PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM (Studi Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2012-2014) - Dwinurcahyo, Ridho; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2016)
The aims of this study are to analyze the effect of Earning per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), dan Debt to Equity Ratio (DER) on Stock Prices. This study was taken because there are still differences between the research study with each other and there is a difference between the real of research data with existing theory. This research was conducted using secondary data. Sampling technique used was purposive sampling. The criteria that needed are mining company whose shares are still actively traded on the Indonesia Stock Exchange, has a data independent and dependent variables for this study, and has a complete annual report for the year 2012-2014. Of the thirty-nine companies, only taken nineteen companies as research samples. The analytical method used is multiple linear regression analysis. The results showed that there are simultaneously influences between Earning per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV), Debt to Equity Ratio (DER) on stock prices. Partially, Earning per Share (EPS), Price Earning Ratio (PER), Price to Book Value (PBV) has a positive and significant impact on stock prices and the Debt to Equity Ratio (DER) has a negative and significant impact on stock prices.